Structural Analysis Of Stretchable Electronics Joint Under Tensile And Vibration Loading - Mustaffa, Nadirah (Universiti Sains Malaysia, 2017)
Solder joint is the major part of electronic devices to form an electrical connection and mechanical bond. Thus, study of electronics joint reliability is significant to determine the ability of the interconnection to maintain its functionality under subjected environments. Reliability of electronics joint is actually can be affected by its structure and materials used. As currently electronic devices is widely applied in automobiles application, the reliability of electronics interconnections under vibration loading is also an issue in this study as its leads to joint failure. Two 3D led with different conductive adhesive electronic joint structure that connected to a circuit model is developed by using Solidworks 2016, whereas ANSYS workbench 16.0 was used to simulate the models. Purpose of this research is to study the structural of conductive adhesive joint, strength and its reliability under vibration load. Two analyses were done, structural analysis and random vibration. Models was simulated in structural analysis and subjected to 1mm/min Y-axis displacement loading to analyze the adhesive joint structure and its strength. The analysis was compared with pull strength test experimental result as verification. Then different adhesive joint material strength was applied in both models to study the relationship between adhesive joint materials with its strength. Models were simulated in random vibration analysis to study the adhesive joint reliability in the frequency ranges 3Hz-500Hz. Structural of adhesive joint was analyzed based on the maximum equivalent stress contour and concentration on the model. Maximum equivalent stress value was analyzed to determine adhesive joint strength and reliability. From the structural analysis it can be concluded that joint structures affect the interconnection strength and higher material strength is more reliable than lower material strength. Random vibration analysis results showed both solder joint model is affected by the excited frequency and failure occurred at the connection between joint and copper pad circuit.